Emigration from Russia: New Trends and Forms 499 Industry and Inter-Industry Associations - Iontsev, Vladimir Alekseyevich; Ryazantsev, Sergey Vasilyevich; Iontseva, Svetlana Vladimirovna (Economy of Regions, 2016)
The subject-matter of this article is migration from Russia. The study deals with current aspects and new forms of emigration. The goal of this paper is to identify new patterns determining the emigration from Russia. The article views the emigration in a broad sense, including, in addition to classic emigration (i.e. leaving the home country for permanent residence in another country), various categories of return migration (labor migration, shuttle traders, seasonal migration, episodic migration, economic tourism, business migration, education abroad, etc.). With the emergence of these new forms and categories, there is a need to clarify the migration concepts. This analysis is built on a broad historical perspective on emigration, which has been a typical phenomenon for Russia over the last three centuries. The article is based on such economic theories, as the human capital theory, new economic theory of migration, Todaro’s economic theory of migration and other. In this article, a variety of methods are used, including historical analogy, statistical and mathematical approaches, sociological and econometric models. The article analyzes the patterns of modern emigration from Russia. It also considers certain aspects in the legal regulation of migration processes, with a focus on emigrants, including potential emigrants. In conclusion, the article notes the need for the state control of emigration processes. This means not so much the improvement of statistical records for this group of migrants, but rather specific government measures aimed at providing the state support to these categories of migrants in order to prevent the nonreturn migration. In other words, it is not aimed at banning the emigration (a measure, the adverse effects of which were noted as long ago as by Mikhail Lomonosov), but at providing the state support to these categories of migrants in order to prevent the non-return migration. The findings of this research can be used in improving the migration policy implemented, in particular, by the Federal Migration Service of Russia.